Meşrubat sanayiinde maliyetlerin oluşumu ve muhasebeleştirilmesi - Aydın, Tuncay (My University, 2004)
Soft drinks industry consists of sodas, fruit juice, and water and mineral water sectors. Soda, coke, fruit flavored sodas, tonic and varieties of these are produced in soda sector. In fruit juice sector, fruit juice, flavored beverages, fruit juice in powder form are produced. And also in water and mineral water production sector includes production of treated water, mineral water and its soda, artificial mineral water and fruit flavored natural mineral water. Accounting is divided into three parts: financial accounting, managerial accounting and cost accounting. While the documents and application rules of financial accounting are stated in the current law, they are determined by the enterprises in cost accounting. The whole of the sacrifices done for the sake of a specific target is called as cost. On the other hand cost accounting is recording, classifying, reporting and interpreting all value actions emerged by production and services and it also means calculation of the costs of products and services according to their amount and type. Cost accounting aims to help private enterprises to calculate the unit costs, control the expenditure, plan and make decisions. Costs can be classified according to their time of account, technical characteristics of production and the way they are calculated. Also we can classify the cost accounting systems according to quality of production activities, costs' time of account and expenditures' time of participation to the costs. The enterprises that are obliged to arrange appendix financial tables must implement the 7/ A option when they are observing the expenses. In the 7/ A option, the costs are recorded to the great book according to the function rule, while the same is done according to the sort rule in 7/ B. Enterprises using 7/ A use the cost accounts in group Nr. 70-78 and the ones using 7/ B use Nr. 79. Each of the expense account groups are classified like costs, cost reflection and difference accounts in the great book. In the production system of soft drinks industry if the serial production system is cost accounting system, then the appropriate system is the order cost accounting system. In industry, both the similar goods and different goods are produced. The products are conserved in the recyclable or in non-recyclable packages. Rules due to bottling, labeling, marking, packaging, transportation and storage of the contents are all stated in the Instruction of Turkish Food Codex. Main component of the soft drinks products is water and it is used in production process after disinfections and refining steps. The accounting of the costs of soft drink industry is as with the accounting of the costs of other production sectors. Meşrubat sanayi; gazlı içecekler, meyve suyu ve benzeri içecekler ile su ve soda sektörlerinden meydana gelir. Gazlı içecekler sektöründe: sade gazoz, kola, meyveli içecek, tonik ve bunların türevleri; meyve suyu ve benzeri içecekler sektöründe: meyve suyu, meyve nektarı, meyveli içecek, aromalı içecek ile meyve suyu tozu; su ve soda sektöründe ise: kaynak suyu, işlenmiş su, maden suyu ve sodası, yapay soda ve meyve aromalı doğal maden suyu üretilir. Muhasebe; finansal, yönetim ve maliyet muhasebesi olarak üç bölüme ayrılır. Finansal muhasebede kullanılan belgeler ve uygulama esasları yasal mevzuatla belirlenirken maliyet muhasebesinde, işletmeler tarafından belirlenir. Bir amaca ulaşmak için katlanılan fedakarlıklar tümüne maliyet; Üretim ve hizmetin gerektirdiği her türlü değer hareketlerini kaydetme, sınıflama, raporlama ve yorumlamayarak, maliyetleri üretilen mal ve hizmetin tür ve miktarına göre hesaplama faaliyetine maliyet muhasebesi denir. Maliyet muhasebesi; birim maliyeti hesaplama, gider kontrolü, planlama ve işletmede alınacak özel kararlara yardımcı olmayı amaçlar. Maliyetleri; genel, hesaplama zamanına, üretimin teknik özelliği ve maliyetlerin hesaplanma şekline göre; maliyetleri muhasebesi sistemlerini ise; üretim faaliyetlerinin niteliğine göre, maliyetleri hesaplama tarihine göre, harcamaların maliyete katılma durumlarını esas alarak sınıflandırmaya tabi tutmak mümkündür. Ek mali tablo düzenleme zorunluluğu olan işletmeler, giderlerin izlenmesinde, 7/ A Seçeneğini uygulamak zorundadırlar. 7/ A Seçeneğinde maliyetler, büyük deftere fonksiyon esasına göre, 7/ B Seçeneğinde ise çeşit esasına göre kaydedilir. 7/ A Seçeneğini uygulayan işletmeler, 70-78 No.lu gruptaki maliyet hesaplarını, 7/ B Seçeneğinİ uygulayan işletmeler ise: 79 No.lu gruptaki maliyet hesaplarını kullanır. Gider hesap gruplarının her biri, büyük defterde: gider, gider yansıtma ve fark hesapları şeklinde bölümlenir. Meşrubat sanayiinde üretim sistemi olarak; seri üretim sistemi, maliyet muhasebesi sistemi olarakda sipariş maliyet sistemi kullanılır. Sanayide hem benzer mamuller, hem de farklı mamuller üretilir. Üretilen mamuller; geri dönüşümlü ve dönüşümsüz kaplarda muhafaza edilir. Mamullerin şişelenmesi, etiketlenmesi, işaretlenmesi, ambalajlanması, taşınması, depolanması ile ilgili kurallar Türk Gıda Kodeksi Yönetmeliğinde belirlenmiştir. Meşrubat sanayiinde üretilen mamullerin ana maddesi kuyu su olup; dezenfekte ve arıtılarak üretime sevk edilir. Meşrubat sanayiinde oluşan maliyetlerin muhasebeleştirilmesi diğer sanayi kollarında meydana gelen maliyetlerin muhasebeleştirilmesi gibidir.
Keywords: Meşrubat Sanayii_Muhasebe; Muhasebe; Yönetim ve yardımcı hizmetler